2023
DOI: 10.1001/jamadermatol.2023.2227
|View full text |Cite
|
Sign up to set email alerts
|

NCSTN In-Frame Deletion in Maltese Patients With Hidradenitis Suppurativa

Abstract: ImportanceHidradenitis suppurativa (HS) is a complex trait that has a monogenic etiology in a subset of patients. Variation in genes that encode proteins of the γ secretase complex, particularly NCSTN, account for few patients who exhibit familial forms of HS. Thus far, extensive genotype-phenotype correlations have been lacking.ObjectiveTo establish the prevalence of the NCSTN:c.671_682del variant and explore potential genotype-phenotype associations in an ethnically Maltese HS cohort.Design, Setting, and Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This study is noteworthy because, until now, all NCSTN variants identified in research participants with HS have been unique to families . The cohort used in the study by Mintoff et al consisted of individuals from 98 unrelated families, suggesting that this single variant is carried by 1 in 20 Maltese individuals with HS. This may help to explain the high prevalence of HS in Malta …”
mentioning
confidence: 96%
See 4 more Smart Citations
“…This study is noteworthy because, until now, all NCSTN variants identified in research participants with HS have been unique to families . The cohort used in the study by Mintoff et al consisted of individuals from 98 unrelated families, suggesting that this single variant is carried by 1 in 20 Maltese individuals with HS. This may help to explain the high prevalence of HS in Malta …”
mentioning
confidence: 96%
“…In this issue of JAMA Dermatology , 2 HS genetic studies are reported. The first study investigates the prevalence of an NCSTN variant (an in-frame deletion) previously identified by the same author group . The second study identifies HS risk variant alleles in a GWAS conducted with nearly 2000 cases.…”
mentioning
confidence: 99%
See 3 more Smart Citations